Complete physical map of the rfb gene cluster encoding biosynthetic enzymes for the O antigen of Salmonella typhimurium LT2. - Brahmbhatt, H N (1988)
Biosynthesis of the Salmonella typhimurium LT2 O antigen is encoded by genes which map in the rfb cluster. The cloning and restriction enzyme analysis of part of this cluster have been described previously (H. N. Brahmbhatt, N. B. Quigley, and P. R. Reeves, Mol. Gen. Genet. 203:172-176, 1986). The entire rfb gene cluster has now been cloned, and a detailed restriction enzyme map has been constructed which has enabled us to map the approximate positions of individual rfb genes.